International round-robin test on an improved indentation fracture (IF) method performed through high-magnification microscopy with a traveling stage. Issue 10 (December 2015) - Miyazaki, Hiroyuki; Yoshizawa, Yu-ichi
Abstract: An international round-robin test on an improved indentation fracture (IF) method was conducted successfully with seven laboratories using solid-phase sintered silicon carbide, silicon nitride, and alumina. An objective lens with a high magnification of either 40× or 50× and a calibrated traveling stage were employed to enable both clear identification of the crack tips in high resolution and precise measurement of the crack length. Misreading of the crack length by each laboratory was reduced compared with the conventional IF method, resulting in a moderate scatter in the indentation fracture resistance ( K IFR ) data collected by the participating laboratories. The coefficient of variance for the three samples was less than 8%, which is comparable to those typical of standard fracture toughness tests such as the surface crack in flexure method and the single-edge V-notch method. Additionally, the results were consistent with those of our previous domestic round robin test, thus confirming the reliability of the improved IF method both internationally and domestically.